The role of employee value propositions and corporate brand preferences in talent attraction - Ferreira, Elizabeth H (Organisational Psychology, 2016)
The ever increasing competition to recruit talented and skilled employees has created the necessity to understand which factors influence an applicant's decision to pursue a job offer from an organisation. Recruitment efforts no longer focus solely on the unemployed job seekers market, but has in recent years extended more aggressively into recruiting students before graduation. Moreover, some authors suggest that 60 % of current employees are passively seeking other employment, which creates opportunities to entice talented employees from competitors. However, it has become exceedingly clear that undifferentiated retention strategies are no longer appropriate or effective. The aim of this study was to develop an understanding of the relative importance that new entry job seekers and passive job seekers, from different demographic groups or cohorts, place on Employee Value Propositions (EVPs) and an organisation's corporate brand when choosing to pursue different job opportunities. A secondary aim of the study was to identify the ideal combination and quantum of EVPs relative to the organisation's corporate brand that may entice potential candidates to pursue a career opportunity within an organisation. The current study adopted a descriptive research design, following a quantitative research approach. Primary data was collected from students, graduates and employed job seekers in their early career stage by means of two online questionnaires (n= 954). The questionnaires were compiled from the total rewards elements included in the World at Work Total Rewards model and were informed by a comprehensive literature review on Employee Value Propositions (EVPs) and Organisation Corporate Brand. Descriptive statistics, t-tests and ANOVAs were used to analyse data collected from Questionnaire 1 and to analyse the data collected with Questionnaire 2. Choice-based conjoint analyses were used to identify the ideal combination and quantum of EVPs relative to the organisation's corporate brand; as well as which of these variables (i.e. EVPs or corporate brand) are considered more important for potential employees. The results obtained from the choice-based conjoint analysis revealed that overall EVP's were considered (relatively) more important than Corporate Brand, while Affiliation (i.e.employee's association with the organisation, person-organisational fit) was considered more important overall than Corporate Brand.